Shigellosis in adults: A retrospective study of clinical and epidemiological features in East London. (December 2019) - McGuire, Emma; Mikhail, Amy; Day, Martin; Serafino-Wani, Robert; Godbole, Gauri
Shigella is a leading cause of gastroenteritis worldwide; however, data on clinical outcomes amongst adults are lacking. All adult cases (>16 years) of Shigella gastroenteritis diagnosed between January 2014 to December 2017 at an East London NHS Trust in the United Kingdom were included. Demographic, clinical, microbiological and whole genome sequencing (WGS) data were retrospectively collected. Shigella spp isolates from 169 cases were identified: S. flexneri 90 (53.3%), S. sonnei 75 (44.9%) and S. boydii 4 (2.0%). The median age was 34 years (IQR 29–45), and 127 (75.1%) were male. S. flexneri cases were more likely to attend accident and emergency (46.7% vs. 25.3%, p = 0.005), be admitted to hospital (26.7% vs. 10.7%, p = 0.01), and receive antibiotics (51.1% vs. 28.0%, p = 0.003) compared to S. sonnei cases. Thirty-two (18.9%) patients were admitted to hospital for a median of five days (IQR 3–8). Where recorded 42/84 (50.0%) reported recent travel. Seventeen (10.1%) patients experienced complications. There were no deaths within one year of diagnosis. Seventy-nine isolates were characterised by WGS. Fifty-seven (72.2%) belonged to known national clusters; 44 (55.7%) involving adult males and 11 (13.9%) travel-associated clusters. We demonstrate the development of severe complications of shigellosis among adults and highlight the changing epidemiology and antibiotic resistance patterns.